Investigating survivorship bias: The case of the 1918 flu pandemic - Joël Floris; Laurent Kaiser; Harald Mayr; Kaspar Staub; Ulrich Woitek (University of Zurich, Department of Economics, 2021)
Estimates of the effect of fetal health shocks may suffer from survivorship bias. The fetal origins literature seemingly agrees that survivorship bias is innocuous in the sense that it induces a bias toward zero. Arguably, however, selective mortality can imply a bias away from zero. In the case of the 1918 flu pandemic, a suppressed immune system may have been protective against the most severe consequences of infection. We use historical birth records from the maternity hospital of Bern, Switzerland, to evaluate this possibility. Our results suggest that a careful consideration of survivorship bias is imperative for the evaluation of the 1918 flu pandemic and other fetal health shocks.
Keywords: I10; I15; I18; N34; J24; 330; Fetal origins hypothesis; 1918 flu pandemic; culling; survivorship bias; Pandemie; Grippe; Pränatale Entwicklung; Langfristige Analyse; Sterblichkeit; Sozialstatus; Schweiz